2000
DOI: 10.1038/modpathol.3880097
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma Expression in Thyroid Neoplasms

Abstract: Retinoblastoma (Rb) mutation in thyroid neoplasia has been identified in a few molecular studies; however, the utility of Rb immunohistochemistry in distinguishing benign and malignant thyroid lesions has not been documented in formalin-fixed, paraffin-embedded tissues. The present study investigated Rb immunohistochemistry in a series of 111 formalin-fixed, paraffin-embedded benign and malignant thyroid lesions. All of the major histologic subtypes were included to detect any heterogeneity in Rb-1 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…The proliferative status and alterations of the cell cycle and retinoblastoma (Rb) pathway in oxyphilic and nonoxyphilic tumors have been assessed in several studies on thyroid cancer (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Several studies on the proliferative activity of oxyphilic tumors demonstrated no differences from conventional follicular adenomas and carcinomas, both well differentiated and poorly differentiated (10,15,22).…”
mentioning
confidence: 99%
“…The proliferative status and alterations of the cell cycle and retinoblastoma (Rb) pathway in oxyphilic and nonoxyphilic tumors have been assessed in several studies on thyroid cancer (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Several studies on the proliferative activity of oxyphilic tumors demonstrated no differences from conventional follicular adenomas and carcinomas, both well differentiated and poorly differentiated (10,15,22).…”
mentioning
confidence: 99%
“…Inactivation of these proteins results in a continuous growth of the thyroid, little affecting its differentiation, function and regulation (Iuliano et al, 2000). There is still a debate on RB1 function in human thyroid tumorigenesis with contradictory results on its loss or overexpression in papillary and follicular carcinomas vs adenomas (Anwar et al, 2000).…”
mentioning
confidence: 99%
“…With respect to ATC, both RB and p53 status has been documented using various molecular techniques, 10,11,19 indicating that RB rather than p53 dysfunction occurs at higher frequency. The present study further emphasizes these observations, as eight of the nine cell lines tested had RB dysfunction, whereas only five of the nine cell lines exhibited p53 pathway dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…9 The RB pathway is impaired in its function in the majority of advanced human cancers, including ATC, regardless of whether RB itself is mutated or not. RB mutations in thyroid neoplasms have been documented in a small number of cases 10 and RB pathway dysfunction appears to be a common feature of thyroid cancer. 11 A number of strategies have been employed to target defects in this pathway with the hope of developing new therapeutics.…”
Section: Introductionmentioning
confidence: 99%